Peningkatan keterampilan berpikir elaboration melalui penerapan model think pair share (tps) dalam pembelajaran ips kelas V sekolah dasar - Debrina, Aldisha Tamara; Istiyati, Siti; Yulianti, Yulianti (Universitas Sebelas Maret, 2022)
The aim of this research is for impoving the elaboration thinking skills by applying think pair share learning model in Social Sciences lessons. This research is Classroom Action Research with two cycles action and each cycles had 4 stages that is planning, action, observation, and reflection. The subjects of this research were students of grade 5th at SD Negeri Jajar 1 No.73 Surakarta on the 2019/2020 academic year with total 27 students. The data collection techniques of this research is the form of interview, observation and elaboration thinking skill tests, and also document studies technique. This research used Miles and Huberman interactive analysis models for the data analysis. The outcome of this research after applying the action was increased from the first condition 58,11 (37%) to 73,74 (52%) in the first cycle, 85,10 (85%) in the second or the last cycle. Based on the outcome of this research, the conclution is the elaboration thinking skills of grade 5thelementary school students in social science learning can be increased after implementing the Think Pair Share learning model.